Revision of the genus Coletinia (Zygentoma: Nicoletiidae) in the Iberian Peninsula, with descriptions of nine new species - Molero, Rafael; Bach, Carmen; Sendra, Alberto; Montagud, Sergio; Barranco, Pablo; Gaju, Miguel (Zootaxa, 2013)
The discovery of several members of the genus Coletinia Wygodzinsky, 1980, from subterranean habitats (endogean and troglobiont), prompted the review of this genus in the Iberian Peninsula. Most of the samples came from caves of the Mediterranean basin of Spain, from Cádiz to the Tarragona province. As a result of this revision, nine new species have been established: C. herculea n. sp., an endogean from Cádiz; C. vergitana n. sp. from the Gádor calcareous mountains in Almería; C. calaforrai n. sp. from the gypsum karst in Almería; C. intermedia n. sp. from caves in Murcia and Alicante; C. diania n. sp., found in the north of the province of Alicante; C. longitibia n. sp. and C. tessella n. sp., both troglobites from Valencia; C. redetecta n. sp. from Castellón caves and finally C. hernandoi n. sp., an endogean from Tarragona. Moreover, Coletinia maggii (Grassi, 1887) is reported for the first time in the Iberian Peninsula, and new data are presented regarding C. mendesi, C. tinautiand C. capolongoi that widen their geographic distribution and enhance the information about their anatomic characteristics and biology. These results increase the number of known species of this genus to 14 in the region and to 21 in the world. The new species are described and compared with the most closely related previously known species of the genus. Characters with the most taxonomic relevance are discussed using optical and scanning microscope studies. A key for the identification of the Iberian Coletinia species and a distribution map including all of them are also provided.